Efeitos de selante de fibrina autólogo na redução de seroma pós-operatório em abdominoplastias - Valentini, Jorge Diego (2020)
Background: abdominoplasty is one of the five most performed plastic surgeries in Brazil and worldwide. It is characterized by aesthetic and functional correction of deformities caused mainly by post-pregnancy status or after major weight loss with significant redundancy of the skin and laxity of the musculoaponeurotic layer. Despite being a low risk surgery, some complications can occur, especially local complications. Among these, seroma is the most common with an average incidence estimated by the literature in 10%. Seroma consists of an exudative liquid collection that accumulates deeply in the undermined areas. Despite being a complication with benign evolution in most cases, it can lead to conditions such as suture dehiscence, necrosis of the dermoadipose flap and local infection. Some measures, such as the use of internal adhesion sutures and the use of compressive postoperative garment, are routinely used by most plastic surgeons to reduce the incidence of seroma, but do not completely prevent his appearance. Fibrin sealants are already used in several aesthetic and reconstructive surgeries with the objective of greater adherence between the flap and deep tissues and less leakage from both blood vessels and lymphatic vessels. The objective of the present study is to evaluate the efficacy of fibrin sealant produced from autologous blood in the prevention of seroma in postoperative period of abdominoplasty. Methods: A prospective, controlled, double-blind clinical study was conducted with consecutive patients who were candidates for abdominoplasty. During surgery, autologous fibrin sealant was applied to only one side of the abdomen, with the other side, isolated by adhesion points across the midline, serving as a control. An ecography exam was performed to objectively assess the thickness of the liquid layer on both sides of the abdomen in the epigastric, umbilical, hypogastric region, right and left iliac fossa between the tenth and fourteenth postoperative day, which comprises the peak phase for incidence of seroma. Results: when comparing the results between the intervention and control sides, a lower value of liquid layer was obtained in the umbilical region on the intervention side compared to the control side (median 0.30mm versus 0.80mm, respectively, P = 0.010). There was also a reduction in the hypogastric region despite having medians equal to 0 on both sides, the values were higher on the control side when compared to the intervention side (P = 0.010). There were no other statistically significant differences, but there was a tendency for less liquid accumulation on the intervention side in the two other regions evaluated. Conclusion: the use of fibrin sealant is a useful measure to decrease the incidence of seroma in the postoperative period in abdominoplasty.